Socialization of the "Three Green Pillars" Program in Empowering Dharma Wanita - Ardelia Putri Zahrah; Iffahtul Nadiyah Tampilang; Safira Simbala; Dendra Hala; Elsa Fira Kasim; Rahmawati Tiara Arsad; Laudia Aprilia Mokoginta; Shakilla Putri Lomotu; Sri Anitya Paputungan; Ahmad Alifat Sabana (Unram Journal of Community Service, 2025)
This research was conducted to explore the environment and culture of Tobongon Boltim village. This research also aligns with the theme assigned by the university to our Community Service Program students. We used observational, ethnographic, and historical methods. We used observational methods, observing directly how the community engages in gardening and plastic waste processing. In addition to observational methods, we also employed ethnographic methods, focusing on the community and specific groups in understanding natural or non-chemical pesticides. Furthermore, we used historical methods, which involved listening to stories from local residents who frequently visited our post. Using these three methods, we discovered that the Tobongon village community rarely uses natural pesticides and disposes of a lot of used cooking oil, which then hardens and clogs the drains. We also heard that children in Tobongon village hold daily TPQ (Quran study parks) during the day. Therefore, we took the initiative to create Syu'batul al-Lughatul Arabiyah in the afternoons to help the children learn to write the hijaiyah letters correctly. In addition to teaching the hijaiyah alphabet, we also teach Arabic vocabulary to familiarize them with vocabulary in other languages. Throughout our work program, the Tobongon village community has been very enthusiastic and has provided significant assistance. Nearly all of our programs have been implemented successfully.